1993
DOI: 10.3109/08941939309141617
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microporous Polyurethane Vascular Graft: In Vivo Evaluation of the UTA Prosthesis Implanted as Infra-Renal Aortic Substitute in Dogs

Abstract: A novel microporous polyurethane blood conduit developed at the University of Texas at Arlington was implanted as an infra-renal substitute in dogs. The prosthesis was fabricated by precipitating a solution of the polymer with dry nitrogen onto a rotating mandrel. The grafts were sterilized either by gamma radiation (series I) or ethylene oxide (series II); they were implanted for the following prescheduled periods: 4, 24, 48 hours, and 1 week (short-term) and 2, 4 weeks, 3 and 6 months (medium-term). The thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…On the other hand, this study showed that both PEU membranes demonstrated good hemocompatibility and low levels of complement activation. However, these results must be interpreted with caution as Tecoflex‐based and PEU Mitrathane (Biomer‐like) arterial grafts were shown to be highly thrombogenic (19,20). The authors of these studies recognized, as have others, that the type of graft wall structure and topography also contribute to the thrombogenic behavior of these prostheses.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, this study showed that both PEU membranes demonstrated good hemocompatibility and low levels of complement activation. However, these results must be interpreted with caution as Tecoflex‐based and PEU Mitrathane (Biomer‐like) arterial grafts were shown to be highly thrombogenic (19,20). The authors of these studies recognized, as have others, that the type of graft wall structure and topography also contribute to the thrombogenic behavior of these prostheses.…”
Section: Discussionmentioning
confidence: 98%
“…Because of its excellent elasticity and biocompatibility,15–22 polyurethane has been widely regarded as the best candidate to solve the compliance problem. Many polyurethane vascular grafts have been fabricated using different methods 23.…”
Section: Introductionmentioning
confidence: 99%
“…However, graft thrombosis is still a serious clinical problem in spite of continuous improvements in graft development [14]. Polyurethane has been used to solve the thrombus problem due to its excellent elasticity and biocompatibility, and a microporous structure can be successfully fabricated in the wall using different methods [15][16][17][18][19][20][21][22]. The porosity of commercially available polyester (Dacron) knitted vascular grafts can be reduced by coating or sealing with a novel ionic urethane, to improve their blood-proof property.…”
Section: Introductionmentioning
confidence: 99%